Institutional support of Ukraine’s foreign trade: the context of the Middle East - Duginets, Ganna; Omran, Hossain Z. (WUNU, 2021)
Conceptual approaches to stimulating trade cooperation of Ukraine and the Middle East countries are investigated. The paper determines the existent potential for furthering cooperation in the region and outlines its main prospects. The current system of institutional support of Ukraine’s foreign trade is analysed. In light of the worsening economic conditions in the world and falling indicators of export potential in Ukraine in 2019 and 2020, development and implementation of institutional support for the strategy of promoting domestic goods on foreign markets and supporting their production becomes a priority. The authors substantiate the main factors that should be taken into account by Ukrainian producers when entering the Middle East markets. An hierarchy of institutional support goals is suggested in terms of Ukraine’s cooperation with the countries of the region in foreign trade.
Keywords: institutional support; trade cooperation; stimulation of export; Ministry of International Affairs; the Middle East countries